2021
DOI: 10.1155/2021/8841281
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Awaji Criteria and Revised El Escorial Criteria in the Diagnosis of Amyotrophic Lateral Sclerosis (ALS) at First Visit in a Tunisian Cohort

Abstract: Background. Amyotrophic lateral sclerosis (ALS) is a fatal disease whose diagnosis and early management can improve survival. The most used diagnostic criteria are the revised El Escorial criteria (rEEC) and Awaji criteria (AC). The comparison of their sensitivities showed contradictory results. Our study aimed to compare the sensitivities of these two criteria in the diagnosis of definite ALS, at first visit, in a Tunisian hospital cohort. Materials and Methods. This was a retrospective study including 173 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…The study involved 47 patients with clinically definite, probable, or possible ALS according to [6]. The average duration of the disease, i.e., the time from the onset of the first paresis to the time of the study, was 31 months.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study involved 47 patients with clinically definite, probable, or possible ALS according to [6]. The average duration of the disease, i.e., the time from the onset of the first paresis to the time of the study, was 31 months.…”
Section: Methodsmentioning
confidence: 99%
“…Until recently, the revised El Escorial criteria and the Awaji criteria remained the "gold standard" for the diagnosis of ALS [6]. In 2019, ALS experts established new Gold Coast criteria, which a large cross-sectional study confirmed to be more accurate and sensitive than their predecessors [7].…”
Section: Introductionmentioning
confidence: 99%
“…1 (10) In this study total of 28(65.1) had definite ALS and presented with median (IQR), 6(5-10) months of illness. They were generally cervical phenotype, 31(72.1%), and they had ALS functional rating score, median (IQR) of 27 (25)(26)(27)(28)(29)(30)(31)(32). (Table 2).…”
Section: Demographic and Clinical Profile Of The Participantsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted August 8, 2023. ; https://doi.org/10.1101/2023.08.04.23293649 doi: medRxiv preprint the life expectancy of ALS patients [29]. The most used diagnostic criteria are the revised El Escorial criteria (rEEC) and Awaji criteria (AC), has sensitivity ranges from 40-70%, which increases with the progression of the disease [30]. Electrophysiology may help diagnose early ALS, as some electrophysiologic findings may appear earlier.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…Beim Vergleich der Awaji-Kriterien mit den revidierten El-Escorial-Kriterien zeigte eine Metaanalyse eine verbesserte Sensitivität der Awaji-Kriterien (81,1%) im Vergleich zu den revidierten El-Escorial-Kriterien (62,2%) bei vergleichbarer Spezifität 24 . Bezogen auf die Kategorie „sichere ALS“ zeigte eine Untersuchung in einer tunesischen ALS-Kohorte eine signifikant verbesserte Sensitivität der Awaji-Kriterien im Vergleich zu den revidierten El-Escorial-Kriterien für die Frühphase der Erkrankung (61 vs. 12,2%) und sowohl für den spinalen (70,2 vs. 39,8%) als auch bulbären (65,6 vs. 42,1%) Erkrankungsbeginn 25 . Der Unterschied war nicht mehr vorhanden, je länger die Erkrankung andauerte (mehr als 24 Monate: 78,2 vs. 69,1%).…”
Section: Differenzialdiagnostik Der Alsunclassified